Análisis de los servicios turísticos en la Ruta del Río del cantón Quevedo, 2020 - Luna de Jesús, Laleska Dayana (2021)
The River Route belongs to Quevedo, Los Ríos province, Ecuador, enriched with flavors and ancestral customs, recognized for its agricultural production and for its export of bananas and cocoa, with an unmatched historical cultural potential, which is used by the providers of tourist services to provide a better quality in its production. The objective of the research was to analyze the tourist services on the route of the river of the Quevedo canton of the year 2020, to determine the strengths and weaknesses in the tourist services offered, and thereby verify if they will have good productivity over time, accommodating to the needs and demands of today's tourist. The project will benefit the service providers registered in the cadastre of the town of the river route, as this will help a positioning at a national and international level, to include quality in products and services, with which Quevedo be one of the most important towns in offering tourism with a quality seal.